Identification of Gradient Promoters of Gluconobacter oxydans and Their Applications in the Biosynthesis of 2-Keto-L-Gulonic Acid - Chen, Yue; Liu, Li; Yu, Shiqin; Li, Jianghua; Zhou, Jingwen; Chen, Jian (Frontiers in Bioengineering and Biotechnology, 2021)
The acetic acid bacterium Gluconobacter oxydans is known for its unique incomplete oxidation and therefore widely applied in the industrial production of many compounds, e.g.,. 2-keto-L-gulonic acid (2-KLG), the direct precursor of vitamin C. However, few molecular tools are available for metabolically engineering G. oxydans, which greatly limit the strain development. Promoters are one of vital components to control and regulate gene expression at the transcriptional level for boosting production. In this study, the low activity of SDH was found to hamper the high yield of 2-KLG, and enhancing the expression of SDH was achieved by screening the suitable promoters based on RNA sequencing data. We obtained 97 promoters from G. oxydans’s genome,, including two strong shuttle promoters and six strongest promoters. Among these promoters, P3022 and P0943 revealed strong activities in both Escherichia coli and G. oxydans, and the activity of the strongest promoter (P2703) was about threefold that of the other reported strong promoters of G. oxydans. These promoters were used to overexpress SDH in G. oxydans WSH-003. The titer of 2-KLG reached 3.7 g/L when SDH was under the control of strong promoters P2057 and P2703. This study obtained a series of gradient promoters, including two strong shuttle promoters, and expanded the toolbox of available promoters for the application in metabolic engineering of G. oxydans for high-value products.